MOTIVASI ORANGTUA BERAGAMA MUSLIM MENYEKOLAHKAN ANAK DI SEKOLAH DASAR (SD) KALAM KUDUS PEKANBARU - Lusi Simatupang; M. Razif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Education is one thing that is needed in today’s modern times. Education consists of three kinds of formal, informal and non formal. Formal education is one of the fundamental things that must be taken by all children in Indonesia in accordance with the national education goals is for the intellectual life of the nation. In general, parents want their children to be smart and can be a source of pride for the family. In elections where his sosn was educated parents consider good schools and is considered to be able to educate their children well. Given the many standing in Pekanbaru international schools, religious schools, private schools and public schools. Muslim religious parent who prefer to send their children to primary school Kalam Kudus is one private school based on the teachings of religion is protestant Christianity. Therefor, the formulation of the problem in this research are : 1. What motivation causes parents who send their children to religious muslim kalam kudus elementary school ? 2. How socio cultural background of muslim parents who send their children to kalam kudus elementary school ? Subjects in this study were religious muslim parents who send their children kalam kudus elementary school in pekanbaru as many as five people. The method in this study ia qualitative research method, namely the outlines of the interview respondents. The results of this study is the motivation of parents who send their children to religious muslim kalam kudus elementary school is comprised of intrinsic motivation and extrinsic motivation. Intrinsic motivation that parents want their children to be a smart kid and has a lot of knowledge and because elementary school is one of the holy word of school discipline and have the quality and the quality is very good whereas extrinsic motivation is that the distance is not to far away from school and wants to raise the degree of their social status. Socio cultural backgrouns of muslim parents who are different rom one another, and every parents wants only the besr for their children’s education. Keyword : Motivation Parents, Education, Religion